Impact of Hotel Service Quality on Attracting Tourist and Achieving their Loyalty: A Case Study of Hotel Industry in Kurdistan Region - Ahmed, Younis; Al-jaf, Walla; Faeq, Dalia (The Arab Journal of Administration, 2020)
The Kurdistan region of Iraq has great potential to attract a large number of tourists. In fact, five-star hotels in the Kurdistan attempts to get greater market share and maximizing hotels profits by attracting more tourists and achieving tourist loyalty, by providing high level and different types of services. The main objective of this study is to find out the impact of service quality on attracting tourists and tourist loyalty in the five-star hotels in Sulaimani province/Kurdistan Region- Iraq. To achieve this objective, the study adopts descriptive analytical method (DAM), and was based on the previous studies and literature review related to the subject of the study. Furthermore, the primary data are collected from a survey conducted during the period from 25/11/2016 to 25/12/2016, on (70) guests who stayed in five-star hotels. In alignment with the research objectives and methodology, this study developed the following hypothesis “there is a strong and significant relationship between the quality of service and attracting tourists and tourist loyalty in five-star hotels”. Furthermore, the regression model interpretation ability for all service quality dimensions represented in (R²) coefficient was 0.85 which indicating that 85% of changes in attracting tourists and tourist loyalty are interpreted by service quality dimensions. To sum up, a set of necessary recommendations for hotels was formulated to attract more tourists through providing more and high quality of services.